2020
DOI: 10.1186/s13643-020-01386-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparing effects of continuous glucose monitoring systems (CGMs) and self-monitoring of blood glucose (SMBG) amongst adults with type 2 diabetes mellitus: a systematic review protocol

Abstract: Background: Continuous glucose monitorings (CGMs) have been used to manage diabetes with reasonable glucose control amongst patients with type 2 diabetes (T2D) in recent decades. CGMs measure interstitial fluid glucose levels to provide information about glucose levels, which identify fluctuation that would not have been identified with conventional self-monitoring. Self-monitoring of blood glucose (SMBG) is a classical tool to measure glycaemic changes. However, the effectiveness of glucose control, hypoglyce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Previous reviews on diabetes technology have mostly focused on the effectiveness or efficacy of the technology in adult populations [26][27][28], with some also including youth [29]. While various studies have focused on experiences with diabetes technology and particularly experiences with technology in young people with T1DM, reviews of such study findings are still lacking.…”
Section: Technology For Diabetes Managementmentioning
confidence: 99%
“…Previous reviews on diabetes technology have mostly focused on the effectiveness or efficacy of the technology in adult populations [26][27][28], with some also including youth [29]. While various studies have focused on experiences with diabetes technology and particularly experiences with technology in young people with T1DM, reviews of such study findings are still lacking.…”
Section: Technology For Diabetes Managementmentioning
confidence: 99%
“…To assess the variability in blood glucose levels, we selected a more representative and simple calculation of MBG, SDBG, MAGE, and HbA1c [18][19][20][21][22][23][24] . Wu et al [12] showed that blood glucose in the poor glycemic control group was higher at 10:30, with a downward trend to the lowest level at 12:30; blood glucose continued to rise to a peak at 14:30, then dropped to 16:30, and then rose again.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review still in press, the PROSPERO study [47], will compare the various forms of CGM systems (i.e. flash CGM, rtCGM, retrospective CGM) versus SMBG among adults with T2D.…”
Section: Cgm and T2dmentioning
confidence: 99%